Assistance for village owned enterprises through information technology-based institutions in Sandang Pangan Village, Buton Selatan Regency - Nastia Nastia; L.M. Azhar Sa'ban; Muh. Rizal Ardiansyah Putra; Jumadil Jumadil; Finangsih Finangsih; Rezky Mahendra Alfayeed; Latif Latif; La Gufran (Universitas Muhammadiyah Magelang, 2023)
The purpose of this community service is to assist village owned enterprises (BUMDes) through two approaches, namely strengthening BUMDes institutions based on collaboration and increasing the competence of BUMDes resources with entrepreneurial innovation. The method used in this community service activity is carried out in three stages, namely observation, workshop, and mentoring. Through this PKM, BUMDes Lamando Jaya was able to formulate a potential map and create a business plan document that can be applied to BUMDes’ governance. BUMDes administrators are able to bridge community programs as a village government agenda. Also through this program, BUMDes managers can optimize social media as a means of tourism and business promotion through educating content creation and photography techniques.